Oxfendazole: a promising agent for the treatment and control of helminth infections in humans. Issue 1 (2nd January 2019) - Gonzalez, Armando E.; Codd, Ellen E.; Horton, John; Garcia, Hector H.; Gilman, Robert H.
ABSTRACT: Introduction : Oxfendazole (methyl [5-(phenylsulphinyl)-1H benzimidazole-2-yl] carbamate) has a particularly long metabolic half-life in ruminants, and its metabolite fenbendazole also has anthelminthic action. A very limited number of drugs are available for the treatment of some zoonotic helminth infections, such as neurocysticercosis and echinococcosis. More recent work has expanded oxfendazole's nonclinical safety profile and demonstrated its safety and bioavailability in healthy human volunteers, thus advancing the possibility of a new and greatly needed option for antiparasitic treatment of geohelminths and tissue parasites. Areas covered : The present article reviews evidence supporting the safety and efficacy of oxfendazole against both gut and tissue dwelling helminths in animals, as well as more recent safety and pharmacokinetic data supporting its potential for use in human parasitoses. Expert commentary : The pharmacokinetics, safety, and wide spectrum of efficacy of oxfendazole are consistently demonstrated in intestinal helminth infections of animals as well as in tissue dwelling larval cestode and trematode infections in diverse animal species. Now supported by first-in-human safety and pharmacokinetic data, oxfendazole becomes a promising alternative to the limited portfolio of antiparasitic drugs available to treat helminthic diseases of humans.